Impact of different placement depths on the crestal bone level of immediate versus delayed placed platform-switched implants. Issue 7 (July 2018) - Madani, Elika; Smeets, Ralf; Freiwald, Eric; Sanj, Maryam Setareh; Jung, Ole; Grubeanu, Daniel; Hanken, Henning; Henningsen, Anders
Abstract: Purpose: The preservation of peri-implant bone is one requirement for long-term success of dental implants. The purpose of this study was to evaluate the impact of subcrestal placement on the crestal bone level of immediate versus delayed placed implants after loading. Materials and methods: In this retrospective study, data of 159 patients who received 330 implants was analyzed. Implants were placed subcrestally, crestally or supracrestally into fresh sockets or healed sites. Vertical bone level height was assessed radiographically and implants were followed up annually. The influence of patient and implant related risk factors for peri-implant bone loss was evaluated using a linear mixed model. Results: Depth of implant placement was significantly correlated with peri-implant bone loss (P = 0.001, 95% CI). Least effective loss of crestal bone was determined when implants were placed between 1 mm and 1.99 mm subcrestally. Smoking significantly enhanced the risk of peri-implant bone loss (P = 0.04, 95% CI). Immediate implant placement was not positively correlated with peri-implant bone loss (P = 0.51, 95% CI). Conclusion: Within the limits of this study, implant placement 1.08 mm subcrestally may be recommendable in order to avoid supracrestal expositions of platform-switched titanium implants over time.